Analysis of biaxial fatigue limit models for cases with circular notches. (September 2022) - Chaves, V.; Navarro, A.; Susmel, L.; Taylor, D.
Highlights: Multiaxial fatigue models for notches are analysed. The geometry is an infinite plate with a circular hole. The evolution of the predictions with an increasing hole radius is not monotonic. This non-monotonic evolution is not observed experimentally. Abstract: This work shows an analysis of several models of multiaxial fatigue for notches: Navarro-Rios' model, which analyses the interaction between the crack and its associated plastic zone with the material microstructural barriers, and three models that combine a critical volume method for notches with a critical plane model for multiaxial fatigue in unnotched solids. Specifically, the application of these models for the prediction of the fatigue limit for a plate with a circular hole subjected to axial, shear and in-phase biaxial cyclic loading is studied. The effects of two parameters are analysed: the radius of the hole and the relationship between the torsional and axial fatigue limits. For all the analysed models, cases are observed in which an increase in the hole radius produces an increase in the predicted fatigue limit, that is, the evolution of the fatigue limit with an increasing hole radius is not always monotonically decreasing, as would be expected. These effects, which we have called "humps" because of their appearance on the prediction graphs, mainly occur in shear loading. No humps were observed in the studied experimental results, but the number of available experimental results is too small to assure this tendency. The results shown in the work indicate that a greater knowledge of the physics of multiaxial fatigue in notches is necessary to achieve models that are capable of providing increasingly accurate predictions.